2015
DOI: 10.1093/aob/mcv118
|View full text |Cite
|
Sign up to set email alerts
|

The compounding effects of high pollen limitation, selfing rates and inbreeding depression leave a New Zealand tree with few viable offspring

Abstract: The results suggest that for these populations, over half of the seeds produced are genetically doomed. This reduction in the fitness of progeny due to reduced pollinator service is probably important to population dynamics of other New Zealand species. More broadly, the results suggest that measures of seed production or seedling densities may be a gross overestimate of the effective offspring production. This could lead to cryptic recruitment failure, i.e. a decline in successful reproduction despite high pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 68 publications
3
18
0
Order By: Relevance
“…Meanwhile, the transhumant herds graze on the drove road only at the end of the spring, following a "green wave" when the plants have already grained, relatively untouched during the flowering phase. While a greater coefficient of inbreeding is a genetic indicator that can be related to pollinator limitation (Turner et al 1982, Dutech et al 2005, Van Etten et al 2015, the structural role of drove roads as grassland corridors crossing agricultural landscapes has been proved to be determinant in supporting pollinator services (Hevia et al 2016), which our study confirms. This result goes along other studies that have observed provision of heterogeneity at the landscape level because of the drove road's structural role, translated in higher biodiversity levels (Azcárate et al 2013a;Hevia et al 2013).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Meanwhile, the transhumant herds graze on the drove road only at the end of the spring, following a "green wave" when the plants have already grained, relatively untouched during the flowering phase. While a greater coefficient of inbreeding is a genetic indicator that can be related to pollinator limitation (Turner et al 1982, Dutech et al 2005, Van Etten et al 2015, the structural role of drove roads as grassland corridors crossing agricultural landscapes has been proved to be determinant in supporting pollinator services (Hevia et al 2016), which our study confirms. This result goes along other studies that have observed provision of heterogeneity at the landscape level because of the drove road's structural role, translated in higher biodiversity levels (Azcárate et al 2013a;Hevia et al 2013).…”
Section: Discussionsupporting
confidence: 74%
“…Due to the effect of pollinators activity to crossing system (i.e. selfing, partial selfing or outcrossing, Turner et al 1982, Dutech et al 2005, Van Etten et al 2015, for the analysis of F IS the amount of grasslands in 500-m radius circles centered in sampling points (in percentage, logtransformed to achieve normality) was also included. The landscape descriptors (distance and percentage of grasslands) were standardized and centered to interpret model coefficients as standardized effects.…”
Section: Relationships Of Genetic Descriptors With Environmental Factorsmentioning
confidence: 99%
“…Thus, the smaller inbreeding coefficient observed along the drove road indicates a relevant role played by them in providing pollination services. While a greater coefficient of inbreeding is a genetic indicator that can be related to pollinator limitation (Van Etten et al 2015), the structural role of drove roads as grassland corridors crossing agricultural landscapes has been proved to be determinant in supporting pollinator services (Hevia et al 2016). This result goes along other studies that have observed provision of heterogeneity at the landscape level because of the drove road's structural role, translated in higher biodiversity levels (Azcárate et al 2013a;Hevia et al 2013).…”
Section: Discussionsupporting
confidence: 53%
“…Recent studies have shown that the majority of angiosperms suffer from pollen limitation [1][2][3] and most of them are self-compatible (SC), which enables selfing and protects against pollinator deficiency [4][5][6]. Selfing may act autonomously, when flowers are structurally adapted to pollen transfer on their own stigma, or when pollinators as pollen vectors transfer pollen within the same flower or inflorescence [7,8].…”
Section: Introductionmentioning
confidence: 99%